One-step synthesis of alkyl 2-chloropyrimido[1, 2-a]benzimidazole-3-carboxylates under catalyst-free: combined experimental and computational studies. Issue 36 (2nd September 2015) - Liu, Yang; Xia, Guoming; Luo, Chao; Sun, Jianqi; Ye, Benfei; Yuan, Yanli; Wang, Hongming
Graphical abstract: Abstract: An efficient method for the preparation of pyrimido[1, 2- a ]benzimidazole derivatives utilizing squaric acid dichloride has been developed at room temperature without catalyst. This method provided a rapid synthesis of pyrimido[1, 2- a ]benzimidazole system. The result indicates that those expeditious reactions could be carried out only in the presence of alcohols, affording the corresponding alkyl 2-chloropyrimido[1, 2- a ]benzimidazole-3-carboxylates. Furthermore, the yield of products seems to be closely relevant to the steric hindrance of the added alcohols. On the basis of experimental and theoretical analyses, a plausible mechanism has been proposed and corroborated through DFT calculations for exploring a practical way to efficiently synthesize those highly versatile substituted homologs.